Reflections on palliative sedation. (January 2019) - Twycross, Robert
'Palliation sedation' is a widely used term to describe the intentional administration of sedatives to reduce a dying person's consciousness to relieve intolerable suffering from refractory symptoms. Research studies generally focus on either 'continuous sedation until death' or 'continuous deep sedation'. It is not always clear whether instances of secondary sedation (i.e. caused by specific symptom management) have been excluded. Continuous deep sedation is controversial because it ends a person's 'biographical life' (the ability to interact meaningfully with other people) and shortens 'biological life'. Ethically, continuous deep sedation is an exceptional last resort measure. Studies suggest that continuous deep sedation has become 'normalized' in some countries and some palliative care services. Of concern is the dissonance between guidelines and practice. At the extreme, there are reports of continuous deep sedation which are best described as non-voluntary (unrequested) euthanasia. Other major concerns relate to its use for solely non-physical (existential) reasons, the under-diagnosis of delirium and its mistreatment, and not appreciating that unresponsiveness is not the same as unconsciousness (unawareness). Ideally, a multiprofessional palliative care team should be involved before proceeding to continuous deep sedation. Good palliative care greatly reduces the need for continuous deep sedation.